Preferential Inspection of Views of 3-D Model Heads. (November 2013) - Harries, Mark H; Perrett, David I; Lavender, Alan
The importance of different perspective views for the recognition of model heads was studied. In experiment 1 subjects were instructed to learn the appearance of six heads placed individually on a turntable free to rotate through 360°. Subjects did not distribute their time evenly but focussed their inspection on particular views (the full face view and a view close to the profile). Despite differential inspection of these two views during the learning phase, the face, half profile, and profile views were recognized with equal efficiency in a subsequent recognition task with static views. Experiment 2 used the inspection paradigm to investigate view preference during the recognition of heads from memory. In this experiment subjects were asked to learn the appearance of three heads each seen rotating at an even speed. In a subsequent retrieval task the subjects actively inspected six model heads on the turntable and were asked to differentiate the three heads previously seen rotating from three novel heads. The pattern of inspection in this retrieval task was equivalent to that in experiment 1. Results suggest that during the encoding into memory subjects construct descriptions of specific prototypical views of the head and that descriptions of these same views are preferentially utilised during recognition.